Strategi Penterjemahan Nilai dan Kepercayaan dalam Novel Sungai Mengalir Lesu (Jurnal Bahasa, 2013)
This article discusses the translation of mentifact elements, namely beliefs and values, from Malay into English. The examination focuses on the strategies used for translating mentifacts as well as the factors affecting the choice of strategies. The data used for the analysis were taken from the novel Sungai Mengalir Lesu by A. Samad Said (1967), which had been translated by Aveling (1981). This study utilises the documentary and instrumental approaches as introduced by Nord (1997) to examine the translation strategies. The concept of situational meaning by Larson (1984), the definition of values and beliefs by Katan (2004), and the definition of mentifacts by Huxley (1957) have also been utilised in order to identify the values and beliefs elements, as well as the messages contained within those elements in the source text. It is revealed that the values and beliefs elements in the source language, which share a similar cultural semantic field with the values and beliefs in the target language tend to be conveyed back into the translated text using the documentary approach. On the other hand, the values and beliefs elements in the the source language, which do not exist in the target language's are often translated using the instrumental approach.Keywords: culture; mentifacts; documentary translation; instrumental translation